2013
DOI: 10.1007/s12070-013-0689-8
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Nasal Nitric Oxide Measurement with Computed Tomography Findings in Chronic Rhinosinusitis

Abstract: Nitric oxide (NO) is a biological messenger produced by mammalian cells serving various functions including regulation of blood flow, platelet function, immunity, and neurotransmission. The paranasal sinuses and nasal mucosa are a major source of exhaled NO. The aim of the study is to compare the nasal NO (nNO) levels in patients with chronic rhinosinusitis with those of common cold patients and controls and to correlate CT scores with nNO levels. The nasal concentration of NO was measured by electroluminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 33 publications
3
23
3
1
Order By: Relevance
“…This suggests that patients with more severe sinus disease had lower nNO levels. This is consistent with 2 prior studies that also showed a negative correlation between nNO and disease severity on CT . In contrast, there was no correlation between the baseline nNO and SNOT‐22 score.…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that patients with more severe sinus disease had lower nNO levels. This is consistent with 2 prior studies that also showed a negative correlation between nNO and disease severity on CT . In contrast, there was no correlation between the baseline nNO and SNOT‐22 score.…”
Section: Discussionsupporting
confidence: 91%
“…The lack of NO may play a role in the pathogenesis of this disease, so this change in nNO amount can be easily measured and provides a valuable non-invasive marker for chronic rhinosinusitis. Overall, significantly lower levels of Nasal NO were reported in the patients with chronic rhinosinusitis (CRS) (irrespective of nasal polyps or allergic 18 indicated that, the lack of nNO is attributed to the pathogenesis of chronic rhinosinusitis. Furthermore, Bommarito, et al 19 and Liu, et al 13 stated that nNO levels were significantly lower in patients with CRSwNP than that in patients with CRSsNP and controls, these significant differences in the nNO levels have been used to distinguish between chronic rhinosinusitis patient with nasal polyps (NP) and chronic rhinosinusitis patient without nasal polyps (NP).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that the study of Jeong, et al 17 recorded significantly lower amounts of nNO in chronic rhinosinusitis (CRS) with polyps and allergic rhinitis than controls. Dabholkar, et al 18 reported that there was no difference in levels of NO between healthy control and common cold patients, whereas nNO levels was significantly lower in patients with chronic rhinosinusitis. Bommarito, et al 19 and Liu, et al 13 postulated that nNO levels could be used as marker to distinguish between chronic rhinosinusitis with nasal polyps (CRSwNP) and chronic rhinosinusitis without nasal polyps (CRSsNP).…”
Section: Nno= Nasal Nitric Acid Crswnp= Chronic Rhinosinusitis With mentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23] On the other hand, researchers have reached consensus on the role of nitric oxide (NO), given the direct links between low exhaled NO levels and clinical status deterioration and imaging findings. 24,25 Given that NO appears to be crucial for the optimal functioning of the mucociliary system, 26 we might interpret the observed lung abnormalities in patients with CRS as arising from dysfunctional ciliary status.…”
mentioning
confidence: 99%